Isu-isu Strategik dan Implementasinya dalam Lembaga Pendidikan Islam - Faizin, Husnul (Lembaga Yasin AlSys, 2023)
The focus of this article is to describe strategic issues and their implementation in Islamic educational institutions. The role of Islamic educational institutions in improving education is very strategic because the aim of education is basically to humanize humans, or to elevate human dignity or